Effect of Chronic Exposure of Cadmium Chloride in Drinking Water on Structural and Functional Aspects of Thyroid Gland in Mature Male Rabbits - Samir H. Cheyad; Kalisa K. Khudier; Khtan A. AL-Mzain (College of Pharmacy University of Baghdad, 2017)
The effect of chronic exposure to two different levels of cadmium chloride (CdCl2) 30 ppb and 40 ppb in drinking water for 12 weeks on thyroid function of mature male rabbits was studied. Eighteen mature male rabbits  were randomly divided into three groups (each of six ) , control group (group I ): were offered ordinary tap water , and treated groups (II and III ) were offered tap water containing 30ppb and 40 ppb respectively for 12 weeks .Serum concentration of  thyroxin (T4 ) and triiodothyronine (T3) were measured every six weeks ,as an index  of  thyroid function , further more ,  section of thyroid gland were prepared for histological studies. The results showed that  chronic exposure of male rabbits to two  different levels of  CdCl2  caused significant decrease (p<0.05) in serum T3 and T4 in both treated groups in compared with control group, in addition, there were histological changes in thyroid gland of treated groups manifested by hyperplasia with presence of large number of varying size of microfollicels and hypertrophic thyrocytes, small colloid with little secretion . Key wards: Cadmium, Thyroid gland, Thyroxin, Triiodothyronin, Thyrocyt